2018
DOI: 10.1097/sla.0000000000002065
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Acute Pancreatic and Peripancreatic Collections Occurring in Patients With Acute Pancreatitis

Abstract: Patients with severe AP and delayed hospitalization more often develop acute collections. Pancreatic pseudocysts are a rarity in acute interstitial pancreatitis. A majority of patients with necrotising pancreatitis will develop ANC, more than half of whom will develop WON. Delay in hospitalization and higher baseline necrosis score predict need for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 38 publications
2
63
1
2
Order By: Relevance
“…This study is a retrospective analysis of prospectively collected data comparing the various outcome parameters of the two main etiologies of AP, namely, GS and alcohol. These two etiologies account for 70-80% of all AP, 5,6,15 as was also the case in the current study where 80.1% of the patients either had GS or alcohol as the etiology. The etiologies of alcohol-and GS-related AP have a clear gender bias as has been established in previous multiple studies, with males having a higher percentage of alcoholrelated AP and females a higher percentage of GS-related AP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study is a retrospective analysis of prospectively collected data comparing the various outcome parameters of the two main etiologies of AP, namely, GS and alcohol. These two etiologies account for 70-80% of all AP, 5,6,15 as was also the case in the current study where 80.1% of the patients either had GS or alcohol as the etiology. The etiologies of alcohol-and GS-related AP have a clear gender bias as has been established in previous multiple studies, with males having a higher percentage of alcoholrelated AP and females a higher percentage of GS-related AP.…”
Section: Discussionsupporting
confidence: 82%
“…4 Although various etiologies have been described to cause AP, the two most common etiologies accounting for 70-80% of all the cases are gallstones (GSs) and alcohol. 5,6 Identification of the etiology may help in the better formulation of treatment strategies or prevention of recurrence, although the pattern of conservative management of the ongoing attack of AP is similar across etiologies. Whether etiology contributes to the outcome in patients with AP is an unresolved issue.…”
Section: Introductionmentioning
confidence: 99%
“…reported that patients with AIP had a higher intervention rate than those with EXPN. Their PCD rate was otherwise also higher than reported in other long‐term follow‐up studies of AIP . Our results suggests that patients with EXPN alone have a more severe clinical course and require more aggressive management compared to those with AIP.…”
Section: Discussioncontrasting
confidence: 46%
“…1 The rising incidence and severity of AP probably reflects rising incidence of obesity in children and increasing awareness among pediatricians. 5 However, about 40% of pseudocysts develop symptoms requiring drainage. Complications in the delayed phase (>4 weeks) of AP include infection and development of pancreatic fluid collections (PFC).…”
Section: Introductionmentioning
confidence: 99%
“…Acute fluid collections (<4 weeks old) are usually asymptomatic and most resolve spontaneously. 5 However, about 40% of pseudocysts develop symptoms requiring drainage. 6 Drainage of PFC can be achieved by endoscopic, percutaneous or surgical methods.…”
Section: Introductionmentioning
confidence: 99%